“Llegaron a esta ciudad con repique general de todas sus campanas”, la ciudad virreinal en dos textos conventuales (Revista de Crítica Literaria Latinoamericana, 2022)
This article analyzes two New Spains conventual texts from the first half of the 18th century, the Crónica del convento de Santa Brígida, written collectively by the nuns, and the Vida de la VM Sor María Antonia de la Madre de Dios, signed by the last of his confessors, José Jerónimo Sánchez de Castro. These texts allow to set the importance that the cloister had for the royal city as a space for symbolic projection, which actively participated in the creolization process. At the same time, it was considered a place of memory and female intervention that allows us to read the gender relations that are inscribed in the urban space.
Keywords: convent; chronicle; life; city; gender